2023
DOI: 10.1038/s41557-023-01149-6
|View full text |Cite
|
Sign up to set email alerts
|

Rupturing aromaticity by periphery overcrowding

Abstract: The balance between strain relief and aromatic stabilization dictates the form and function of non-planar π-aromatics. Overcrowded systems are known to undergo geometric deformations, but the energetically favourable π-electron delocalization of their aromatic ring(s) is typically preserved. In this study we incremented the strain energy of an aromatic system beyond its aromatic stabilization energy, causing it to rearrange and its aromaticity to be ruptured. We noted that increasing the steric bulk around the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 78 publications
0
14
1
Order By: Relevance
“…Surprisingly, we find that the total ring current in the S 1 and T 1 states can be reversed from aromatic to antiaromatic by movement along the Kekulé vibration (∼2300 cm –1 ), i.e., by changing the amount of bond-length alternation . These aromaticity reversals require a relatively small amount of energy, in contrast with previous reports which require a change in the electronic state, molecular charge or composition, , or involve a high-lying transition state , or a highly strained geometry . To our knowledge, the only comparable low-energy aromaticity reversal involves a conformational equilibrium between Hückel antiaromatic and Möbius aromatic conformers in a hexaphyrin derivative. , …”
Section: Introductioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Surprisingly, we find that the total ring current in the S 1 and T 1 states can be reversed from aromatic to antiaromatic by movement along the Kekulé vibration (∼2300 cm –1 ), i.e., by changing the amount of bond-length alternation . These aromaticity reversals require a relatively small amount of energy, in contrast with previous reports which require a change in the electronic state, molecular charge or composition, , or involve a high-lying transition state , or a highly strained geometry . To our knowledge, the only comparable low-energy aromaticity reversal involves a conformational equilibrium between Hückel antiaromatic and Möbius aromatic conformers in a hexaphyrin derivative. , …”
Section: Introductioncontrasting
confidence: 83%
“…19 These aromaticity reversals require a relatively small amount of energy, in contrast with previous reports which require a change in the electronic state, 20−23 molecular charge 24−26 or composition, 27,28 or involve a highlying transition state 29,30 or a highly strained geometry. 31 To our knowledge, the only comparable low-energy aromaticity reversal involves a conformational equilibrium between Huckel antiaromatic and Mobius aromatic conformers in a hexaphyrin derivative. 32,33 The simplicity and unique electronic structure of cyclocarbons makes them an interesting testing ground for theoretical methods.…”
Section: Introductionmentioning
confidence: 96%
“…A previous report on the fluorescent properties of hexaphenylbenzene and its homologues of varying central ring size (cyclopropene, cyclopentadiene, and cycloheptatriene) demonstrated that the fluorescence emission wavelength depends upon three factors in the crystalline phase: (i) the extent of interdigitation of the phenyl substituents in the crystal, (ii) the size of the cyclical core, and (iii) the conformational flexibility of the molecule, all of which dictate the intermolecular and intramolecular interaction interphenyl interactions in the crystal. , The increased conformational freedom of the seven-membered core in Ph 7 C 7 H (Figure ), together with the out-of-plane bond angles provided by the aliphatic carbon center in the ring, permits the formation of an intramolecular, transannular T -shaped phenyl dimer (involving Ph 3 and Ph 7 , Figure ), which gives rise to fluorescence from a relaxed excited state. Computed structures of the excited state show a shortened transannular interphenyl interaction compared with the ground state structure, demonstrating the importance of the flexibility of the central ring to the photophysical properties of these systems …”
Section: Introductionmentioning
confidence: 99%
“…The data from Table 1 show, that according to all employed aromaticity indicators, the presence of phenyl groups does not considerably affect the intensity of cyclic electron conjugation within the Ge 3 N 3 ring. [33] Like in molecule a, molecules c-e also exhibit very weak global and π-only electronic circulations, which are mainly localized on the N atoms (Figure S23). Further, calculated ring current strengths, NICS zz (1) and MCI values clearly show that the extent of cyclic electron delocalization in c-e is negligibly small and very similar to that found in a (Table 1).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%